Permainan Bola Bakar terhadap Hasil Belajar Gerak Dasar Manipulatif Siswa Kelas V di SDN Kramat Jati 02 Pagi - Ramdani, Devita Rizki; Rizal, Bayu Thomi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The objective of this research is to investigate the impact of the burning ball game on the learning outcomes of fundamental manipulative movements among fifth-grade students at SDN Kramat Jati 02. This study employs a Quasi-Experimental quantitative research approach, utilizing a Posttest Only Design framework. The sample used in this research is a saturated sample. To assess validity, the point biserial correlation formula was applied to 40 multiple-choice questions, resulting in 35 valid questions and 5 invalid ones. Reliability testing, conducted using the KR-20 formula, yielded a result of r_count > r_table, specifically 0.628 > 0.361, indicating that the data is reliable. Further data analysis involved a normality test using the Liliefors test, where post-test results for the experimental class showed L_0 < L_1 (0.160 < 0.161) and for the control class, L_0 > L_1 (0.137 < 0.161), suggesting that both datasets are normally distributed. The homogeneity test, performed using Fisher's test, indicated F_count < F_table (1.019 < 1.8583), confirming homogeneity in the variance distribution of the group data. Conclusion, Hypothesis testing via the t-test revealed that r_calculated > t_table (9.26 > 2.002), leading to the rejection of H_0 and acceptance of H_1. Key Word : learning outcomes, the burning ball game, sports education